Encyclopedia of computer art [ - Lyman, Marylynn (New York : Learning Press, 2014)
This is an integrated Encyclopedia of Computer Art
1. Computer art -- 2. Computer graphics -- 3. ASCII art -- 4. Computational photography (artistic) and demoscene -- 5. Algorithmic art and fractal art -- 6. Graphic art software -- 7. Spriting and pixel art -- 8. Generative art and computer animation -- 9. ANSI art and motion graphics
Keywords: Computer art